Karakterisasi Kitin dan Kitosan Asal Limbah Rajungan Cirebon Jawa Barat - Emma Rochima (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2007)
The aim of the research was to characterize chitin and chitosan from byproduct of meat crab’s Cirebon canning industry. The preliminary research included chitin flour production. Later on, production and characterization of chitin and chitosan. Characteristics of chitin and chitosan included solubility, degree of deacetylation, intrinsic viscosity and molecular weight. Degree of deacetylation was analyzed by First Derivative Ultra Violet Spektrofotometry, intrinsic viscosity by Ubbelohde viskometry, and molecular weight by Mark-Houwink equation. The result showed that characteristics of chitin and chitosan that included solubility, degree of deacetylation, intrinsic viscosity and molecular weight were 28 %, 39.02 %, 8.57 ml/g, 11 x 103 and 79.39 %, 70.70 %, 6.93 ml/g and 8.75 x 103 respectively. Characteristic of chitosan was suitable for food field application.